STUDI IMPLEMENTASI PEMBELAJARAN MODEL SISWA INKLUSI DI SDS MUTIARA HATI PONOROGO - Dian Puspita Sari; Fuad Fitriawan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2021)
Inclusive education is education for children with special needs so that they can study together with regular children in general. One school that implements inclusive education is SDS Mutiara Hati Ponorogo. Students with disabilities can study together with regular children without being discriminated against. The form of learning model applied in this school pays attention to the condition of the child. With the existence of inclusive schools, it can help children with special needs to get the same place to learn as other regular children and can bring the development of children with special needs to be better. Based on the results of the data analysis, it was concluded that (1) the learning process of inclusive students at SDS Mutiara Hati Ponorogo, namely inclusion students accompanied by a special companion teacher, learning in the same class with regular children and for the gradation is lowered, (2) the form of learning model Inclusion students who are applied at SDS Mutiara Hati Ponorogo are paying attention or adjusted to the conditions of their students by being monitored by psychologists and also the principal, and (3) the impact of implementing the learning model for inclusive students at SDS Mutiara Hati Ponorogo, namely that the development is getting up to the class the better and able to develop its potential.